Metodologia para levantamentos de cargas de incêndio em edificações residenciais - Jose Edier Paz Hurtado (2013)
For the study of fire safety in the constructions is fundamental to know the fire load present in the compartments, whereas it has a direct relation with temperatures that can affect the structures. This work presents the development of a methodology to accomplish the lifting of fire loads in residential constructions. This Methodology is based on photographic records and visual information, for inventory of fuel items present in the compartment. A sampling methodology is also presented in this work classifying the households of Belo Horizonte, Minas Gerais State, in four classes or construction patterns, in order to scientifically validate the data collection in the different classes. Finally, we present a case study surveys of fire loads applying the methodology developed. In this case study, it could be noted that the households of popular class, with areas between 36 m² and 40 m², they have the same amount of furniture as a household of the middle class and upper class, with areas between 41 m2 and 65 m2. However, the specific fire load in a residence of popular class is higher for have a smaller area than a domicile of the middle and upper classes. In popular class, the measurements realized in 6 households showed that the average specific fire load is about 384,08 MJ/m2, while for the high class the measurements in 6 households resulted in a average specific fire load about 318,25 MJ/m2 and the luxury class, the value is about 388,50 MJ/m2 , this result was found in measurements conducted in 3 households. From this information, it can be conclude that the average values of specific fire loads in all classes doesn`t show any higher values than the prescribed by Brazilian standard ABNT NBR 14432, and the upper class is the one that presents the value closest to 300 MJ/m2.